Response to Carboplatin and Paclitaxel in the treatment of hereditary breast ovarian cancer syndrome (HBOC): a case report - Mehmood, Faisal; Touseef, Mumtaz; Ashraf, Amna; Ali Rai, Izza (Journal of the Pakistan Medical Association, 2024)
The co-occurrence of primary breast cancer and primary ovarian cancer is an exceptional hereditary phenomenon and results from inherent mutations in critical genes like BRCA1/2, PALB2, TP53, CHEK1, and ATM. We present here a unique case of hereditary breast-ovarian cancer syndrome (HBOC) reported in Combined Military Hospital, Lahore, Pakistan. It was marked by pathogenic variants in RAD51D, PALB2, CHEK1, and TP53 genes. Remarkably, the patient exhibited an outstanding response to the chemotherapy agents, Carboplatin and Paclitaxel. This dynamic treatment not only led to nearly complete remission of high-grade ovarian serous cancer but also triggered regression in grade-2 invasive ductal breast cancer after just a few rounds of chemotherapy. Consequently, what started as palliative care evolved into a curative triumph. Keywords: Hereditary breast ovarian cancer, Breast cancer, Ovarian cancer, HBOC, BRCA, PALB2, Chemotherapy, Carboplatin, Paclitaxel.